Long term follow-up concerning safety and efficacy of novel adhesion prophylactic agent for laparoscopic myomectomy in the prospective randomized ADBEE study. (August 2016) - Cezar, Cristina; Tchartchian, Garri; Korell, Matthias; Ziegler, Nicole; Senshu, Kazuhisa; De Wilde, Maya Sophie; Herrmann, Anja; Larbig, Angelika; De Wilde, Rudy Leon
Abstract : We conducted a prospective randomized single blind – subject study in the University Clinic of Gynecology of Pius-Hospital Oldenburg. The primary objective of the ADBEE study was to assess the safety and manageability of ADBLOCK when used as an adjunct to laparoscopic surgery for the primary of myomas in women wishing to improve pregnancy outcomes. The study population included 32 women aged between 18–45 years, in good general health condition, who have not completed their family planning and who are undergoing primary ('virgin') laparoscopic myomectomy with an aim to improve pregnancy outcomes. The patients were randomized in 2 groups, ADBLOCK arm with 21 patients and surgery only arm with 11 patients. The study was single blind – subject and the investigators were blinded to treatment group assignment until completion of uterine suturing and prior to removal of the endoscope. A vigorous follow-up of subjects was organized, focusing on its two critical characteristics: completeness and duration. Completeness represented the percentage of subjects who returned to every planed follow – up appointments. The patients were evaluated in a specific period of time, which defined the duration of follow-up. Safety of the ADBLOCK was estimated after analyzing and documentation of any adverse events occurred, clinical and physical examination of patients as well as evaluation of laboratory measures. There were 25 adverse events reported in ADBLOCK treatment group and 12 events in NO-ADBLOCK group over the 24-months treatment. All adverse events in both treatment arms were not anticipated, with all events in the ADBLOCK group being resolved. At 28 days, there was no significant difference in proportion of events between the two treatments (p = 0.440). Overall, the number of events reported was low and the severity of events was generally mild with an unlikely or no relationship to treatment. There were no unanticipated device related adverse events seen in both treatment groups over the immediate post-operative period or during the 24 months follow up period. By 12 weeks all patients reported their wound as healing well or healed and at 6 months all wounds were reported as healed. There were no differences between both treatment groups regarding the use of painkillers over 24 months follow up period. This clinical first – in – human study, sustained by a rigorous follow-up of the subjects has demonstrated that ADBLOCK is a safe product, presenting no additional safety risk or burden to the patients over surgery alone. The device was relatively easy to use, with a low device failure rate that had no impact on the surgical procedures. Highlights: We conducted a prospective, randomized, single-blind ADBEE study, sustained by a rigorous follow up care of the subjects. The long follow up was focused on its two critical characteristics: completeness and duration. In terms of safety, the follow up allowed to monitor the postoperative recovery as well as to diagnose and manage any possible adverse events. First – in – human clinical study for ADBEE provided evidence of safety and good manageability of ADBLOCK.